Penyelesaian Masalah Persediaan Bahan Baku Kopi di Kukang Coffee Cafe dengan Pendekatan Primal Simpleks - Pesta Gultom; Honesty Sembiring; Putri Jelita; Maria Lumbanbatu; Yesi Septiani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Kukang Coffee Cafe is a small business engaged in the Food and Beverage (FnB) sector. This study aims to optimize raw coffee bean inventory management at Kukang Coffee Cafe to minimize costs and prevent stockouts. The main challenges faced are fluctuating coffee bean demand and the costs associated with ordering and storage. The Primal Simplex approach is utilized to develop a mathematical model capable of determining optimal coffee bean order quantities and efficient torage policies. Historical sales data, ordering costs, and holding costs were collected from Kukang Coffee Cafe as a case study. The analysis results demonstrate that the application of the Primal Simplex model successfully identified the most cost-effective ordering and storage combination, leading to a significant reduction in total inventory costs while ensuring adequate stock availability. This study provides practical contributions to Kukang Coffee Cafe in improving operational efficiency and profitability through better inventory management.